Análisis del impacto del gasto militar en la deuda pública en Ecuador, periodo 1990-2021 - Maldonado Chamorro, Antony Jorihel (2024)
Public debt has been a constant concern in our country, reaching 62.1% of GDP in 2020, tripling the levels recorded in 2013. In this context, the present work proposes to analyze the impact of military spending on public debt in Ecuador, period 1990-2021. Statistical information is collected from databases of the World Bank and the Economic Commission for Latin America and the Caribbean (ECLAC). Through an econometric model of time series, specifically using a model of Autoregressive Vectors (VAR) to evaluate long-term relationships and a model of Error Correction Vectors (VEC) to analyze short-term connections, the causal relationship between public debt, military spending, economic growth, inflation and arms exports and imports is also estimated, to establish long-term policies that reduce debt levels. The results show that the evolution of these variables tends to experience fluctuations over time, through the VAR and VEC model, a short- and long-term impact was determined between military spending, economic growth, inflation, arms exports and imports with respect to debt. Likewise, a unidirectional connection was found in which public debt influences inflation and export variables, and in turn, military spending affects debt. It is suggested to apply effective fiscal policies, focusing on optimal management of national income and directing strategic investments to boost growth and strengthen security, reducing dependence on debt collection.